2006
DOI: 10.1017/s0022215106001174
|View full text |Cite
|
Sign up to set email alerts
|

Management of the transgender voice

Abstract: Transsexualism is a condition involving a paradoxical feeling of belonging to the opposite sex. Acquiring a sex-appropriate voice is a crucial part of the patient gaining acceptance in their new gender. Speech and language therapists and otolaryngologists play an important role in influencing communication behaviour in transgender patients by altering the fundamental frequency of speech to one acceptable for the patient's sex. Review of the literature suggests that speech and language therapy is successful at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 11 publications
0
21
0
5
Order By: Relevance
“…Studies have demonstrated the importance of speech-therapy services to transgender/transsexual individuals (Carew, Dacakis, & Oates, 2007;Davies & Goldberg, 2008;Hooper & Hershberger, 2012;McNeill, 2006;Pitts et al, 2009;Soderpalm, Larsson, & Almquist, 2004;Wagner, Fugain, Monneron-Girard, Cordier, & Chabolle, 2003). Some authors believe that an increase in awareness in the scope of practice of speech-language pathology among the LGBT population will result in an increase in the awareness of speech services and referrals from physicians (Soderpalm et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have demonstrated the importance of speech-therapy services to transgender/transsexual individuals (Carew, Dacakis, & Oates, 2007;Davies & Goldberg, 2008;Hooper & Hershberger, 2012;McNeill, 2006;Pitts et al, 2009;Soderpalm, Larsson, & Almquist, 2004;Wagner, Fugain, Monneron-Girard, Cordier, & Chabolle, 2003). Some authors believe that an increase in awareness in the scope of practice of speech-language pathology among the LGBT population will result in an increase in the awareness of speech services and referrals from physicians (Soderpalm et al, 2004).…”
mentioning
confidence: 99%
“…Studies have demonstrated a disconnect between objective measures of treatment efficacy and subjective reports by transgender/transsexual individuals Van Borsel, DeCuypere, Rubens, & Destaerke, 2000). Subjective criteria may be more useful for assessing success from speech therapy than objective assessments (McNeill, 2006;McNeill, Wilson, Clark, & Deakin, 2008). Satisfaction with health care has been shown to be determined through personal interactions (Kelly & Robinson, 2011;Pitts et al, 2009).…”
mentioning
confidence: 99%
“…The literature also indicates that surgery is not sufficient to shape a female voice given that its action occurs only at the larynx level . In addition, satisfaction with the voice is not exclusively related to the change in f0 but to other aspects, such as the intonation, magnetic resonance, and adoption of the vocabulary literacy …”
Section: Discussionmentioning
confidence: 99%
“…Der Abbau der Brustresonanz, die Entwicklung der Kopfresonanz und der Behauchtheit, die typisch f ü r Frauen ist, kann therapeutisch verst ä rkt werden. Die stimmliche Betreuung bei Transsexuellen erfordert deswegen eine intensive Zusammenarbeit von Logop ä den und Klienten [9] . In vielen F ä llen ist aber die mittlere Sprechstimmlage der Betroff enen so tief, dass der H ö rer immer die Stimme des Gespr ä chpartners als m ä nnliche Stimme einstufen wird.…”
Section: Physiologie Der Stimme ▼unclassified
“…Au ß erdem besteht bei Frauen ein physiologisch inkompletter Schluss im hinteren Bereich der Stimmritze (Glottis), welcher die charakteristische Behauchtheit in dem weiblichen Stimmklang verursacht. Neben der Grundfrequenz gibt es jedoch auch andere Eigenschaften einer Stimme, die typisch f ü r M ä nner und typisch f ü r Frauen sind[8,9] , so z. B. die Modulation, d. h. die Melodie oder der Umfang, in dem sich die Grundfrequenz beim Sprechen bewegt.…”
unclassified